Mikroflora Jamur Produk Kakao Kering Serta Kemungkinan Penghambatan Jamur Penghasil Toksin oleh Bakteri Asam Laktat dan Bacillus Spp. - Anton Rahmadi (Jurnal Riset Teknologi Industri, 2016)
Mycotoxins contamination in sun dried cocoa has become a concern in public health  but  it has not been  studied  thoroughly  yet.    This research  aimed  to understand the ecology of fungal contamination in relation to the occurrence of toxigenic  metabolites  in  Indonesian  and  Australian  fermented  cocoa.     The beans  were  surface  disinfected  with  0.4%  chlorine  prior  to  deposite  onto Dichloran   18  %  Glycerol  Agar  (DG-18.  OXOID).     Total  fungal  count  was obtained  from serial  dilutions  on  DG-18 medium.    Streaking  onto  Dichioten Rose Bengal Chloramphenicol  Agar (DRBC, OXOID) purified a specific mould colony.   Simultaneously.  Aspergillus  sec. Flavi colonies were confirmed  using Aspergillus  Flavus  Parasiticus  Agar  (AFPA.  OXOID).    The confirmatory  test was  mainly   based  on  morphological   examinalion   under  phase   contrastmicroscope.   Fungal population  in Indonesian beans varied belween  10’4 – 105cfu/g, while the populations on Queensland beans were consistently low (<100-   2.5  x  102  cfu/g).    However.  there  was  a  high  incidence  of  potentiallymycotoxiqenic filamentous  fungi on all bean samples.   The main species wereAspergillus  flavus, Aspergillus  niger. Aspergillus  wentii. Aspergillus  clavatus. Penicillium citrinum, and Penicillium spinolosum.   The beans from Queensland gave  high  counts  of  Bacillus  species   and  lactic  acid  bacteria  and  it  is suggested   that   they   served   as  natural   biocontrol   againts   against   the filamentous fungi.